2017
DOI: 10.1093/ntr/ntx048
|View full text |Cite
|
Sign up to set email alerts
|

In Their Own Words: Young Adults’ Menthol Cigarette Initiation, Perceptions, Experiences and Regulation Perspectives

Abstract: In this first qualitative study of menthol cigarette use among young adults, we found further evidence that menthol cigarettes can act as starter products because they are perceived as easier to smoke and taste and smell better than non-menthol cigarettes. We also add to the literature in finding that menthol cigarettes are perceived by young people who smoke menthol cigarettes as delivering satisfaction with fewer cigarettes, being accessible as "loosies", and being popular among their peers. Many did not und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 28 publications
6
38
0
Order By: Relevance
“…This idea of capsules being a cigarette for new smokers ties in with industry documents that suggest that product modifications increase appeal among starter smokers. 17 It is also consistent with research in the US, with young adult menthol smokers suggesting that capsule cigarettes would attract beginners, 10 and research in Mexico, with adolescents found to be more interested in trying cigarettes with capsules than without them. 9 With innovation fundamental to value growth for tobacco companies and younger people most receptive to such innovation, 18 the capsule segment has been a welcome success story for tobacco companies.…”
Section: Yum That Is Not Going To Help Me Quit (16-17 Female C2de)supporting
confidence: 69%
See 3 more Smart Citations
“…This idea of capsules being a cigarette for new smokers ties in with industry documents that suggest that product modifications increase appeal among starter smokers. 17 It is also consistent with research in the US, with young adult menthol smokers suggesting that capsule cigarettes would attract beginners, 10 and research in Mexico, with adolescents found to be more interested in trying cigarettes with capsules than without them. 9 With innovation fundamental to value growth for tobacco companies and younger people most receptive to such innovation, 18 the capsule segment has been a welcome success story for tobacco companies.…”
Section: Yum That Is Not Going To Help Me Quit (16-17 Female C2de)supporting
confidence: 69%
“…This is similar to findings from another qualitative study 8 but contrasts with survey research, where those who smoked capsule cigarettes were more likely to perceive their brand as less harmful than those who did not. 10 It may be that perceptions that capsules can reduce risk are associated with use. Nevertheless, our findings are generally consistent with industry reports that factors such as innovation, interactivity and personalisation are the greatest drivers of growth.…”
Section: Yum That Is Not Going To Help Me Quit (16-17 Female C2de)mentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that young adult menthol smokers in the US perceive Camel Crush as fun and entertaining to use, “more minty” than other menthol cigarettes, and a style which would appeal to young, new, or inexperienced smokers. 35 The appeal of this product in Texas may be explained, in part, by its large youth population, but may also be the result of targeted marketing of its Hispanic population, or marketing activity in neighboring Mexico. Research reveals that from 2012 to 2014, while remaining stable in the US, preference for capsules more than doubled in Mexico.…”
Section: Discussionmentioning
confidence: 99%